To evaluate the effectiveness of a structured educational program on knowledge about hypoglycemia and its management among diabetes patients living in selected urban slums of Durgapur, West Bengal - Arul Mathi A. (International Journal of Community Health Nursing And Practices, 2023)
INTRODUCTION: Diabetes Mellitus (DM) is a significant global health issue characterized by chronic hypoglycemia and an imbalance in the metabolism of carbohydrates, fats, and proteins. It has multiple underlying causes. Hyperglycemia refers to high blood glucose levels, while low blood glucose levels are known as hypoglycemia. Raising awareness about the signs and symptoms of diabetes among individuals with the condition can potentially minimize complications. OBJECTIVES: 1. To evaluate the initial knowledge level of diabetic patients about hypoglycemia and its management, both before and after conducting the pre-test and post-test. (2)To assess the impact of the organised training programme on diabetic patients' understanding of hypoglycemia and how to treat it. (3) To establish a relationship between the selected demographic characteristics of the participants and their initial level of knowledge as measured by the pre-test. RESEARCH METHODOLOGY: The study employed a descriptive research design and utilized a non-probability convenient sampling technique to select a sample of 60 participants. MAJOR FINDINGS OF THE STUDY: Out of 60 samples, majority of samples 35(58.3%) were female & only 25(41.7%) of samples were female. Most of the samples 25(41.7%) belongs age group between 46 to 60 years. About 37(61.7%) of people having history of diabetes in family. About 22(36.7%) of people are using herbal medications & about 38(63.3%) of people are not using any kind of medications. About 32(53.3%) of people are having no any history of diabetes. CONCLUSION: According to the study's findings, diabetic patients had somewhat acceptable knowledge of hypoglycemia. So, diabetes patients need to be aware of how to control hypoglycemia by receiving health education that will help them learn how to do so and prevent further problems.
Keywords: and proteins; carbohydrates; chronic hypoglycemia; diabetes mellitus; fats